EDUCATIONAL PROBLEMS IN THE NEW ARMENIAN SETTLEMENTS OF THE SYRIAN JEZIRI (1920-1960 years) (EDUCATION IN THE 21ST CENTURY, 2023)
The proclamation of the Turkish Republic by Mustafa Kemal Ataturk did not bring to an end the state policy of Armenian persecution. On the contrary the policy took new shape underpinned by Kemal's homogenization policy for the newly proclaimed state. Thus, as of 1923 new waves of Armenians were forced to leave the eastern areas of the republic and take refuge in Syria. These refugees were the surviving remnants of the Western Armenians who had not yet left their homeland, having disguised themselves and integrated into local Kurdish villages. Yet, due to the homogenization policy and the consequences of the 1925 Kurdish revolt, these Armenians were left with no support as the rebel Kurdish aghas were persecuted and killed by the state. The paper focuses on the exodus of these Armenians who took refuge in northern Syria. The paper describes the relief efforts local Armenian organizations made and the campaign they carried out to muster support and raise funds for settling these refuges in the area and their eventual integration into the newly established Armenian communities.The Armenians who migrated to Syria in 1927-1930 settled mainly in the north-eastern regions of Syria, in Hasichey, Gamishli and Garamanie, and most of them are members of the Apostolic Church and the Armenian Catholic Church. In resettlement, food supply, healthcare and other issues, the issue of children's education and especially language skills was of primary importance, because the language retreat was significant among them, so it was necessary to take urgent measures to save them.The article presents the integration of Armenians, especially the Kurdish-speaking Bsherigs, who took refuge in the Armenian settlements formed in the north-eastern regions of Syria (in Jezire), the organization of educational activities and the problems of teaching in the formed settlements. . . The mission and necessity of the church, national and Sunday schools are an important incentive for Armenian preservation in the Diaspora, also in the struggle of teachers against Arabic speaking and especially Kurdish speakers.Educational problems had to be solved with the help of national and union responsible. However, educational institutions found themselves in extremely bad conditions. They did not have proper structures, there were no textbooks, there were no pedagogues, there was no proper curriculum that could facilitate the teaching process.In the 1950s and 1960s, young men and girls from different settlements of this region went to Aleppo or other higher educational institutions to follow the courses of those institutions, on the condition that after graduation they would return to their place of birth and contribute to the local Armenian schools. But very few returned and some migrated to other countries.
Keywords: Syrian Jezire, immigrant; schools; pedagogues; methodology; church; school; educational